Submandibular Cervical Mass as the First Presenting Sign of FVPTC. A Case Report and Review of Literature (Global Journal of Medical Research, 2020)
Submandibular cervical swellings can manifest with a wide range of differentials which could be congenital, infective, reactive, neoplastic, or metastatic in origin. Here we discuss a case of a 42 year old male patient, who initially presented with a painless mass in the right submandibular region with no other associated symptoms, which on further examination turned out to be metastatic lymphadenopathy. A thorough investigation of the neck was subsequently performed, which lead us to the diagnosis of follicular variant of papillary thyroid carcinoma with submandibular lymphnode metastasis. Thus, the consideration of a metastatic lymph node in the differential diagnosis is always mandatory in the case of a long standing, largely asymptomatic solitary mass in the lateral neck of an adult patient.
Keywords: cervical mass; submandibular swelling; papillary thyroid carcinoma; follicular variant; lymph node metastasis